Readily available drugs and other interventions to potentially improve the efficacy of immune checkpoint blockade in cancer - Coleman, Merissa; Mascialino, Sophia J.; Panjwani, Anusha; Edwards, Emily; Sukhatme, Vidula V.; Gavegnano, Christina; Sukhatme, Vikas P. (Frontiers in Immunology, 2024)
To improve the efficacy of immune checkpoint inhibitors (ICIs) for cancer treatment, various strategies, including combination therapies with repurposed drugs, are being explored. Several readily available interventions with potential to enhance programmed death 1 (PD-1) blockade have been identified. However, these interventions often remain overlooked due to the lack of financial incentives for their development, making them financial orphans. This review summarizes current knowledge regarding off-label drugs, supplements, and other readily available interventions that could improve the efficacy of PD-1 blockade. The summary of each intervention includes the proposed mechanism of action for combination with checkpoint inhibitors and data from animal and human studies. Additionally, we include summaries of common interventions to be avoided by patients on PD-1 blockade. Finally, we present approaches for conducting further studies in patients, with the aim of expediting the clinical development of these interventions. We strive to increase awareness of readily available combination therapies that may advance cancer immunotherapy and help patients today.